Distraction Osteogenesis for Unicoronal Craniosynostosis: Rotational Flap Technique and Case Series. Issue 6 (December 2018) - Brandel, Michael G.; Dalle Ore, Cecilia L.; Reid, Chris M.; Zhu, William; Lance, Samuel; Meltzer, Hal; Gosman, Amanda A.
Abstract : Background: The limitations of the soft-tissue envelope, devascularized bone grafts, and relapse of the deformity are important considerations in the surgical treatment of unicoronal craniosynostosis. The authors report their technique evolution of distraction osteogenesis for treatment of patients with unicoronal craniosynostosis. Methods: Open anterior cranial vault reconstruction combined with internal distraction was used, with the aid of virtual surgical planning. Technique evolution included maximizing bone flap perfusion by means of limited rotational flap osteotomies, and preservation of dural attachments. Clinical and procedural characteristics including distraction protocol, intracranial volume change, efficiency of distraction, transfusion, operative time, length of hospitalization, complications, and postoperative outcomes were analyzed. Results: Sixteen patients with nonsyndromic unicoronal craniosynostosis underwent repair between August of 2013 and December of 2016. Mean age was 9.0 months. Distractors were advanced a mean of 27.1 mm and achieved a cranial volume change of 29.5 percent, with a mean efficiency of 1.3 percent increase per millimeter of distraction. Mean operating time was 169.3 minutes. Complications were predominately related to infections at the distractor site. At most recent follow-up, all patients had a Whitaker grade I result. Conclusions: Distraction osteogenesis can be a safe and effective method of achieving satisfactory aesthetic outcomes and volume expansion for patients with unicoronal craniosynostosis. The technique presented is proposed to maximize bone flap viability and limit relapse of deformity. Further long-term follow-up is needed for definitive comparison with traditional anterior cranial vault reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.This and Related "Classic" Articles Appear on Prsjournal.com for Journal Club Discussions.